Effect of Perlite as Lightweight Aggregate on Seawater-Fly Ash Concrete Compressive Strength and Water Absorption - Isnin, Mohamad Shahril Shafiq; Md Noor, Nurazuwa (Recent Trends in Civil Engineering and Built Environment, 2023)
Concrete production increased and give negative impact to the environment. In this study, the lightweight concrete was designed using eco-friendly materials such as seawater, fly ash (FA), and perlite aggregate. The objective of this study is to determine the compressive strength and the water absorption of the seawater-FA concrete containing perlite as lightweight coarse aggregate. There two (2) stages of mixing process. First stage was the trial mix, where minimum strength of 50 MPa need to be achieved by replacing OPC with FA by 10%, 20% and 30% by weight. Second stage was the mixture with FA obtained in stage 1 and perlite as coarse aggregate replacement at 10%, 20% and 30% by volume, at target strength of 30MPa. Compressive strength test was conducted on 36 samples at 7 and 28 days, while water absorption test was conducted at 28 days of curing ages on 18 samples. By analyzing the result of the trial mix concrete, it was found that the compressive strength test achieved 50 MPa with 30% of FA replacement, meanwhile all FA-seawater mixture with perlite up to 30% replacement achieved 30 MPa. Water absorption, on the other hand, increased as the proportion of perlite increased.